2018
DOI: 10.1097/dcr.0000000000001202
|View full text |Cite
|
Sign up to set email alerts
|

Different Risk Factors for Early and Late Colorectal Anastomotic Leakage in a Nationwide Audit

Abstract: BACKGROUND: Anastomotic leakage remains a major complication after surgery for colorectal carcinoma, but its origin is still unknown. Our hypothesis was that early anastomotic leakage is mostly related to technical failure of the anastomosis, and that late anastomotic leakage is mostly related to healing deficiencies. OBJECTIVE: The aim of this study was to assess differences in risk factors for early and late anastomotic leakage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
130
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(150 citation statements)
references
References 33 publications
9
130
1
3
Order By: Relevance
“…There is no conclusive study in the literature about the superiority of colostomy or protective ileostomy after transit reconstruction surgery …”
Section: Resultsmentioning
confidence: 99%
“…There is no conclusive study in the literature about the superiority of colostomy or protective ileostomy after transit reconstruction surgery …”
Section: Resultsmentioning
confidence: 99%
“…15 In addition, anastomotic ischaemia is considered as a major risk factor for an extraperitoneal AL but not for an intraperitoneal AL. 15 Therefore, prevention of anastomotic ischaemia is a critical step to prevent AL in LAR with extraperitoneal anastomosis. In our meta-analysis, which only included patients who underwent LAR, we found that patients in the ICG group indeed have a lower AL rate (4.65% versus 11.09%) compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…15 Anastomotic ischaemia is also regarded as a major risk factor for an extraperitoneal AL but not for an intraperitoneal AL. 15 Therefore, the application of ICG FA in low anterior resection (LAR) could have a greater clinical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Sparreboom в своем когортном исследовании, так же пришли к выводу, что ИМТ>30 кг/м 2 может чаще приводить к несостоятельности анастомоза (OR, 1,1, p=0,001). Это так же связывают с толщиной мезоколитической клетчатки, повышенным внутрибрюшном давлением при ожирении, что может усложнить формирование межкишечного анастомоза и нарушить микроциркуляцию в данной зоне [2].…”
unclassified